The Teacher’s Perspective on the Impact of Politeness Strategies in the Indonesian English Textbook on Student’s Communicative Competence - Ayu Meiratnasari; Agus Wijayanto; Suparno (Issues in Language Studies, 2020)
The purpose of this study was to investigate teacher’s perspectives of the impact of politeness strategies in the Indonesian English textbooks on student’s communicative competence. The participants were two English teachers who taught in one of the senior high schools in Yogyakarta, Indonesia and five students. Discourse analysis of the interview data was conducted. The results showed that the teachers have a positive point of view about the authority of politeness strategies, reflected in Indonesian English textbooks, on their student’s communicative competence. Unfortunately, the teachers could not explain in more detail the aspects of communicative competence which could be influenced by politeness strategies in the English textbooks. The interviews with the students indicated that politeness strategies reflected in their English textbooks supported the student’s linguistic competence and strategic competence.